A Review On ZigBee Security Enhancement In Smart Home Environment - Md. Azmi, Karnain; Zahriladha, Zakaria (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2015)
M2M is an approach where devices such as sensors and actuators connected with each other or with a computer system for data analysis for producing immediate action. This approach is gaining popularity among consumers and service providers to improve the lives of people. Among the most popular M2M vertical applications today is the Smart Home application. This application was built by several key components which include private local communications network. Wireless Sensor Network or WSN for short is an example of private communication network that is widely discussed these days due to its characteristics of low power, low cost and scalable. In this paper, we focus on ZigBee, a WSN that has received increasing attention from the industry. Low computing power of the ZigBee's sensor node is causing low endurance against network security attacks, thus providing solutions to all types of network security attacks which are likely to cause significant overhead. Hence, it is vital to properly rank security attacks by evaluating their severity and selecting appropriate countermeasures. In this paper, we provide a review on ZigBee networks technology and security requirements which are already embedded within the protocol. We additionally provide the essential data on the different threats and attacks in ZigBee networks technology. Finally, we investigate the three approaches used by different researchers to enhance the resilience of ZigBee networks in handling network attacks. It is believed that the information presented in this paper would benefit other researchers in enhancing the security level of ZigBee networks especially in supporting Smart Home application.